2019
DOI: 10.1249/mss.0000000000001892
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Implications of Diet and Energy Intake during Physical Inactivity

Abstract: Purpose.-Physical inactivity is associated with disruptions in glucose metabolism and energy balance, whereas energy restriction may blunt these adverse manifestations. During hypocaloric feeding, higher-protein intake maintains lean mass which is an important component of metabolic health. This study determined whether mild energy restriction preserves glycemic control during physical inactivity and whether this preservation is more effectively achieved with a higher-protein diet.Methods.-Ten adults (24±1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…More research is needed to examine whether energy restriction could avoid the consequences of acute physical inactivity as suggested in one of the articles reviewed [23]. Nevertheless, there is evidence to support that at lower levels of physical activity, energy intake is dysregulated leading to a positive energy balance [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More research is needed to examine whether energy restriction could avoid the consequences of acute physical inactivity as suggested in one of the articles reviewed [23]. Nevertheless, there is evidence to support that at lower levels of physical activity, energy intake is dysregulated leading to a positive energy balance [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…While higher CRF is associated with better health, lower CRF is associated with increased mortality independently of other risk factors [2]. Several studies [20,[22][23][24] have determined the effects of an acute period of inactivity on VO 2max . Results indicated that following two weeks of physical inactivity VO 2max was reduced when participants maintained their normal diet [20,24], when calorie intake was restricted [23] or when intake was increased by 50% kcal [22].…”
Section: Metabolic Consequences Of Acute Physical Inactivity In Healtmentioning
confidence: 99%
See 2 more Smart Citations
“…Overweight and obesity have been recognized as risk factors for many chronic diseases such as diabetes, cardiovascular diseases, and the metabolic syndrome [1]. The main driver for weight gain is considered to be the medium or long term positive energy balance, usually through consumption of a high-fat diet (HF) [2,3].…”
Section: Introductionmentioning
confidence: 99%